PENGARUH OPERATING LEVERAGE DAN FINANCIAL LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Christian Alan Darma Saputra Mukti; Muhadjir Anwar (Gapenas Publisher, 2023)
Increasing competition between companies to intensifity the demand that each company to be able adaptation with the situation that is happening, so companies can manage the internal functions, they can be superior for the competition they face. Whatever of business is run by the company, especially properti and real estate companies, to manage their operations, they always use the resources and sources of funds they owned ,for the company optimally to obtain maximum profits to increase the growth and sustainability of the company, by increasing the value of the company to be better. One of the companies that can be describe the value of the company is the level of profitability. The high profitabilityit can be reflects the high company value. Internal funds that involve the level of cash flow from income and depreciation of retained expenses generated the company and there are also funds obtained outside company that come from creditors. Capital from creditors is also debt or leverage for the companies, which is can also be referred to as foreign investment